Imunoexpressão das proteínas e-caderina, snail1 e vimentina em neoplasias de glândula salivar - Colares, Débora Frota (2022)
Salivary gland tumors (SGTs) comprise about 2% to 10% of head and neck tumors and are known for their morphologic diversity and biologic behavior. Some features of malignant neoplasms, such as tumor invasion and distant metastasis, might have the participation of epithelial-mesenchymal transition (EMT), event in which proteins like E-cadherin, Vimentin and Snail1 are directly involved. This study aimed to analyze, by means of immunohistochemistry, the expression of these proteins, as well as to relate their expressions to clinical-pathological features of pleomorphic adenomas (PAs), adenoid cystic carcinomas (ACCs) and carcinomas ex-pleomorphic adenomas (CXPAs) located in minor and major salivary glands. This was a semi-quantitatively analysis which comprised 20 PAs, 20 ACCs and 10 CXPAs. Analysis of E-cadherin was made considering membranar and/or cytoplasmatic expression in parenchymal cells. For Snail1, it was considered the positivity in nucleus and/or cytoplasm of parenchymal cells. Vimentin was evaluated in the cytoplasm of fusiform stromal cells. Data were compared and correlated adopting a level of significance of 5% (p ≤ 0,05). Marked immunoexpression for E-cadherin was mostly found in the cytoplasm of non-luminal neoplastic cells in SGTs; membrane reaction for the protein, seen in luminal cells, was higher in malignant tumors (p = 0,041). Snail1 was more expressed in the nucleus, mostly of nonluminal cells of SGTs, with this reactivity being higher in malignant tumors(p = 0,012). Nuclear positivity for this marker was also higher for ACCs and CXPAs when compared with PAs separately (p = 0,037 e p = 0,025, respectively). No significant differences between E-cadherin and Snail1 and other clinical-pathological parameters were found (p > 0,05). Vimentin was seen in the stroma of all cases, being more diffuse and intense in ACCs. No significant differences between this marker and clinical-pathological parameters were found (p > 0,05). Positive correlations between membranar and cytoplasmatic E-cadherin in PAs, ACCs and CXPAs were observed (r = 0,645, p = 0,002; r = 0,781, p < 0,001; r = 0,677 p = 0,031), as well as between nuclear and cytoplasmatic Snail1 and between cytoplasmatic E-cadherin and nuclear Snail1 in PAs APs (r = 0,569, p = 0,009; r = 0,481, p = 0,032). Negative correlations between membranar E-cadherin and cytoplasmatic Snail1 were observed, as well as between nuclear Snail1 and Vimentin in ACCs (r = -0,471, p = 0,036; r = -0,514; p = 0,021). This last correlation and a positive correlation between membranar and cytoplasmatic E-cadherin were also seen when ACCs and CXPAs were grouped (r = -0,457; p = 0,0011; r = 0,746, p < 0,001). These results suggest that the participation of these proteins in EMT might be related to cellular differentiation in PAs and to tumoral progression in malignant tumors. In addition, it can be infered that the expression of E-cadherin and Snail1 in malignant tumors might reflect the plasticity seen in EMT process. Furthermore, the expression of Vimentin in fusiform stromal cells, probably in later stages of EMT, in the stroma of SGTs, is highlighted.